Uji Variasi Konsentrasi Koagulan Kitosan Hasil Pemanfaatan Limbah Cangkang Kepiting Bakau (Scylla Sp) Dalam Penurunan Kadar TSS Pada Limbah Cair Tahu - Maharani, Zulfia; Caniago, Lestari; Syarifuddin; Tugiyo (CV. Multi Kreasi Media, 2024)
Biocoagulant chitosan from mangrove crabs (Scylla Sp) was applied in the coagulation and flocculation process of tofu wastewater treatment. The concentration variations used were 650 ppm, 620 ppm, 590 ppm, 560 ppm, and control with 3 replications. The research results show a decrease in TSS levels in tofu wastewater after treatment (p-value=0.00001). The TSS level before treatment was 1255 mg/L, and after treatment, the highest average was at a concentration of 650 ppm, which became 691 mg/L (45%), and the lowest average decrease was at a concentration of 560 ppm, which became 833 mg/L (33%).